ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN JASA PENDIDIKAN DI MI AL-WATHONIYAH 22 BEKASI - Rahayu, Puji; Nurhasanah, Siti (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The research purposes (1) to identify and describe the data regarding the marketing strategy of education only by MI Al-Wathoniyah 22 Bekasi (2) to describe the SWOT analysis of the marketing strategy for the education services of MI Al-Wathoniyah 22 Bekasi. The method used in conducting this research is a qualitative method. Research data collection is interviews, observations, and document studies. The data analysis technique used is data reduction, data presentation, and finally drawing conclusions. The results show that MI Al-Wathoniyah 22 Bekasi has implemented a marketing strategy for educational services based on market determination, market position and 7p mix. The school has programs that are the flagship of this school so that enthusiasts from the community are quite enthusiastic and the programs owned by the school are an attraction in itself. Not all schools have superior programs owned by MI Al-Wathoniyah 22 Bekasi. The services provided by schools to users of educational services are also quite good. The cooperation that exists between the school, students, and guardians of students is well established so that educational services in schools can run well. MI Al-Wathoniyah 22 Bekasi should further improve its promotional mix by utilizing all existing facilities to be able to attract service customers, attracting enthusiasts not only focusing on quantity but also paying attention to quality. In this way, the achievements of the school will increase even more.